Mechanical properties of polypropylene blended with esterified and alkylated lignin - Maldhure, Atul V.; Ekhe, J. D.; Deenadayalan, E. (Journal of Applied Polymer Science, 2012)
Lignin does not show miscibility with commercial polyolefins. Therefore, industrial waste lignin was modified in two different ways and subsequently blended with commercial polypropylene (PP) up to 25 wt %. A Brabender electronic plasticorder was used for melt mixing at 190 degrees C. The influence of different modifications on the mechanical properties and processing stability was studied for both polymer blends. The blends of PP and lignin modified (esterified) with maleic anhydride showed less deterioration in the mechanical properties compared to blends of PP and alkylated lignin with dichloroethane. Intermolecular interactions between the PP matrix and modified lignin were concluded on the basis of indicative values derived from various relevant theoretical models to the experimental data. (c) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: mechanical properties; miscibility; modification; polymer blends